2008
DOI: 10.1080/15563650701725136
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral air gas embolism from concentrated hydrogen peroxide ingestion

Abstract: Ingestion of even a small amount of concentrated hydrogen peroxide can result in cerebral air gas embolism. Hyperbaric oxygen therapy may be of benefit in reversing the symptoms and preventing permanent neurological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Gas embolism is a potentially catastrophe, though uncommon, event which occurs as the consequence of gas entry into the vasculature [ 1 ]. Hydrogen peroxide is typically benign with mucosal toxicity being the most commonly reported sign [ 2 ]. Direct exposure to hydrogen peroxide may cause cardiorespiratory insufficiency, shock, convulsions, coma, and chemical burns of skin and mucous membranes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gas embolism is a potentially catastrophe, though uncommon, event which occurs as the consequence of gas entry into the vasculature [ 1 ]. Hydrogen peroxide is typically benign with mucosal toxicity being the most commonly reported sign [ 2 ]. Direct exposure to hydrogen peroxide may cause cardiorespiratory insufficiency, shock, convulsions, coma, and chemical burns of skin and mucous membranes [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon contact with the enzyme catalase in the gastric mucosa, H 2 O 2 undergoes rapid decomposition into oxygen and water (2H 2 O 2 → 2H 2 O + O 2 + heat). 4 If the amount of oxygen liberated exceeds the maximum solubility of blood, bubbles migrate through the epithelial interstices and gas embolism may occur, manifesting as pneumatosis 3 or gas within the portal venous system, 5 brain 6 and coronary arteries. 7 Toxicity is also caused by direct caustic injury to the gastric mucosa, resulting in gastritis and potential rupture, as well as cytotoxicity from lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…3,[9][10][11] Three adult cases had complete resolution after HBO. Mullins 9 appears to be the first author to publish such a case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that first-line treatment of acute arterial oxygen embolism following H 2 O 2 exposure is hyperbaric oxygen (HBO). 3 There are no standard guidelines about when to perform diagnostic imaging looking for venous embolism nor is there consensus as to which diagnostic modality should be utilized [i.e., plain films vs. noncontrast computerized tomography (CT)]. Furthermore, there is currently no consensus about what the standard treatment should be if acute venous oxygen embolism is found following H 2 O 2 exposure.…”
Section: Introductionmentioning
confidence: 97%